2014
DOI: 10.1007/s10762-014-0085-9
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz-time domain spectrometer with 90 dB peak dynamic range

Abstract: Many time-domain terahertz applications require systems with high bandwidth, high signal-to-noise ratio and fast measurement speed. In this paper we present a terahertz time-domain spectrometer based on 1550 nm fiber laser technology and InGaAs photoconductive switches. The delay stage offers both a high scanning speed of up to 60 traces / s and a flexible adjustment of the measurement range from 15 ps -200 ps. Owing to a precise reconstruction of the time axis, the system achieves a high dynamic range: a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
75
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(75 citation statements)
references
References 40 publications
0
75
0
Order By: Relevance
“…THz technology is a rapidly expanding field (Jepsen et al, 2011), and several agricultural applications have been identified, including measuring plant drought stress (Born et al, 2014) and leaf dehydration (Castro-Camus et al, 2013), estimating aflatoxin in peanut oil (Chen and Xie, 2014), and other applications summarized by Mathanker et al (2013). Various methods (Tonouchi, 2007) have been developed to generate and detect THz waves, but THz timedomain spectroscopy (THz-TDS) (Vieweg et al, 2014;Withayachumnankul and Naftaly, 2014) is considered the most powerful and widely used scheme. THz-TDS uses ultrashort laser pulses and photoconductive antennas (Hunsche et al, 1998;Moreno et al, 2014;Tani et al, 1997) or nonlinear crystals (Moreno et al, 2014).…”
mentioning
confidence: 99%
“…THz technology is a rapidly expanding field (Jepsen et al, 2011), and several agricultural applications have been identified, including measuring plant drought stress (Born et al, 2014) and leaf dehydration (Castro-Camus et al, 2013), estimating aflatoxin in peanut oil (Chen and Xie, 2014), and other applications summarized by Mathanker et al (2013). Various methods (Tonouchi, 2007) have been developed to generate and detect THz waves, but THz timedomain spectroscopy (THz-TDS) (Vieweg et al, 2014;Withayachumnankul and Naftaly, 2014) is considered the most powerful and widely used scheme. THz-TDS uses ultrashort laser pulses and photoconductive antennas (Hunsche et al, 1998;Moreno et al, 2014;Tani et al, 1997) or nonlinear crystals (Moreno et al, 2014).…”
mentioning
confidence: 99%
“…The measurement method presented here takes advantage of the high output power of the InGaAs photoconductive switches, the detection sensitivity of the Schottky receiver, and the spectral match of both: The output spectrum of the emitter peaks at frequencies around 450 GHz [9], which coincides with the sensitivity range of the Schottky receiver (50-1500 GHz) [20]. In addition, cardboard materials are sufficiently transparent at these frequencies, at least for a sample thickness of a few millimeters.…”
Section: Resultsmentioning
confidence: 98%
“…This concept necessitates a time delay, which presents a bottleneck in terms of measurement speed. Mechanical delays record 10-500 pulse traces/second at most [8,9]. Novel schemes dubbed ASOPS (Basynchronous optical sampling^) [10][11][12] and ECOPS (Belectronically controlled optical sampling^) [13,14] replace the mechanical delay by two synchronized short-pulse lasers.…”
mentioning
confidence: 99%
“…Photoconductive and EO methods are able to provide large detection bandwidth for THz pulses, which is useful for spectroscopy. As for photoconductive sampling, there are many studies and promising results [25][26][27][28][29][30][31][32]. (i) The sensitivity, THz bandwidth and dynamic range of THz pulse detection are improved by fabricating photoconductive antennas on InGaAs/InAlAs multilayer heterostructures [25,26].…”
Section: Time-domain Thz Samplingmentioning
confidence: 99%
“…(v) Novel optical gating technique is used to realize subpicosecond temporal resolution in pulse detection [30]. (vi) Some work is related to adapting photoconductive THz detectors to THz-TDS systems [31,32]. As for EO sampling, similarly, there are various progress such as improvement of detection eiciency [33,34] and dynamic range [35], polarization sensing of THz pulses [36] and a new detection scheme based on the amplitude variation of optical pulse [37].…”
Section: Time-domain Thz Samplingmentioning
confidence: 99%